2020 20th European Conference on Radiation and Its Effects on Components and Systems (RADECS) 2020
DOI: 10.1109/radecs50773.2020.9857725
|View full text |Cite
|
Sign up to set email alerts
|

Total Ionizing Dose Response of Commercial Off-The-Shelf Microcontrollers and Operational Amplifiers

Abstract: The response to total ionizing dose of several microcontrollers and operational amplifiers was evaluated under 60 Co irradiation. The MSP430FR5994 microcontroller and the ADA4622-1 operational amplifier were fully functional after a cumulated dose of 490 krad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In the study conducted by Armani et al [15], a total of four microcontrollers based on FRAM technology and five operational amplifiers, encompassing both CMOS and bipolar designs, underwent total ionizing dose testing. The findings revealed that, in an unbiased mode, the microcontrollers demonstrated impressive TID tolerance, exceeding 490 krad.…”
Section: A Review Of Some Tid Radiation Test Results On Cots Componentsmentioning
confidence: 99%
“…In the study conducted by Armani et al [15], a total of four microcontrollers based on FRAM technology and five operational amplifiers, encompassing both CMOS and bipolar designs, underwent total ionizing dose testing. The findings revealed that, in an unbiased mode, the microcontrollers demonstrated impressive TID tolerance, exceeding 490 krad.…”
Section: A Review Of Some Tid Radiation Test Results On Cots Componentsmentioning
confidence: 99%
“…In order to cover this need, EDF and CEA have developed an autonomous portable dosimeter hardened up to 3 kGy (300 krad), aimed to record temperature and total ionizing dose (TID) levels seen by electric cables installed in nuclear power plants (NPP) [2]. Now, EDF wishes to extend the possibilities of this device by adding a wireless communication capability for transmission of the measurement data to the control room.…”
Section: Introductionmentioning
confidence: 99%